2012
DOI: 10.1051/epjconf/20123906001
|View full text |Cite
|
Sign up to set email alerts
|

AGN with extreme X-ray amplitude variations

Abstract: Abstract. We present active galactic nuclei (AGNs) that have shown extreme amplitude variability in X-rays. These AGN appear as bright for long periods, but then suddenly become extremely X-ray weak sources. Most likely this behavior is due to strong absorption along the line of sight or by relativistically blurred reflection. Two extreme examples are the Narrow Line Seyfert 1 (NLS1) galaxies WPVS 007 and Mkn 335. WPVS 007 is a peculiar AGN because it combines the properties of a normal NLS1 with those of a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Long gaps of several months occur each year when Mrk 335 is unobservable with Swift because of its proximity to the Sun. Mrk 335 came out of the Swift Sun constraint on 16 May 2020 (Grupe et al 2020) and we resumed our monitoring (Figs. 1 and 2).…”
Section: Swift Xrtmentioning
confidence: 99%
“…Long gaps of several months occur each year when Mrk 335 is unobservable with Swift because of its proximity to the Sun. Mrk 335 came out of the Swift Sun constraint on 16 May 2020 (Grupe et al 2020) and we resumed our monitoring (Figs. 1 and 2).…”
Section: Swift Xrtmentioning
confidence: 99%
“…Grupe et al (2001) showed that 4 out of 113 bright RASS objects that were also observed in ROSAT pointings showed dramatic variations. Grupe et al (2012) added another four objects to this list by means of subsequent XMM-Newton and Chandra observations. All but two are narrow-line Seyfert 1 galaxies.…”
Section: A2 Agn With Strong Intrinsic Variationsmentioning
confidence: 99%
“…OJ 287 underwent another similar high optical to X-ray flux in 2020, with the X-ray flux (0.3-10 keV) reaching the second highest reported for this source (Komossa et al 2020(Komossa et al , 2021a. Spectral studies confirm this to be the reemergence of the soft X-ray spectral state (Komossa et al 2017;Grupe et al 2017;Komossa et al 2020, and references therein) with broadband SED similar to the blazars HBL component Prince et al 2021b). The spectral similarity of the broadband emission to the blazars HBL component (Kushwaha et al 2018b as well as the temporal and polarization (Komossa et al 2020, and references therein) behavior points to a jet origin.…”
Section: Introductionmentioning
confidence: 77%
“…It has been very active since mid-November 2015, in the optical wavebands (e.g. Valtonen et al 2016;Gupta et al 2017Gupta et al , 2019 to X-ray energies (Komossa et al 2017;Grupe et al 2017;Kushwaha et al 2018a,b;Kapanadze et al 2018;Komossa et al 2020). These activities have been concurrent with the predicted (and observed) secondary BH impactinduced flares of 2015 and 2019 in the optical and infrared wavelengths (Valtonen et al 2010(Valtonen et al , 2016Dey et al 2018;Laine et al 2020), indicating a connection between the two (Komossa et al 2020;.…”
Section: Introductionmentioning
confidence: 99%